2014
DOI: 10.12691/jfnr-2-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Amino Acid Changes and Crumb Hardness of Enriched Bread with Tench (<i>Tinca</i><i> </i><i>tinca</i><i> </i><i>L.</i>, 1758) Flesh in Turkey

Abstract: The aim of the present study was to evaluate amino acid changes and crumb hardness of enriched bread with tench (Tinca tinca L., 1758) flesh. Bread was formulated with washed fish mince at the ratio of 5%, 10%, 15% and 20% and the amino acid changes and crumb hardness of breads were evaluated. Adding washed fish mince into bread resulted in a significant increase in the protein content. The amount of amino acids such as aspartic acid, glutamic acid, serine, glycine, threonine, arginine, tyrosine, cystine, phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…Pasta products manufactured with wheat contain a limited amount of essential amino acids representing a potential target for the incorporation of protein sources such as fish by-products [15] which are rich in essential amino acids [8]. In agreement with our results, Shogren et al [45] and Ogur [46] reported similar pattern for total EEA and NEAA levels in soybean-fortified spaghetti and bread enriched with Tinca tinca mince, respectively. On the other hand, these authors also reported an increase on tryptophan and phenylalanine contents due to soybean and T .…”
Section: Resultssupporting
confidence: 90%
“…Pasta products manufactured with wheat contain a limited amount of essential amino acids representing a potential target for the incorporation of protein sources such as fish by-products [15] which are rich in essential amino acids [8]. In agreement with our results, Shogren et al [45] and Ogur [46] reported similar pattern for total EEA and NEAA levels in soybean-fortified spaghetti and bread enriched with Tinca tinca mince, respectively. On the other hand, these authors also reported an increase on tryptophan and phenylalanine contents due to soybean and T .…”
Section: Resultssupporting
confidence: 90%
“…Particularly for minerals (such as calcium, phosphorus, and manganese), the main current sources are organic and inorganic salts that are obtained from chemical synthesis [8]. Consequently, the application of functional ingredients in food was previously reported, for example, n-3 fatty acids were enriched in meat products [9], dairy products were fortified in calcium [10], and baked products were enriched in amino acids [11]. Furthermore, the development of dietary supplements such as n-3 fatty capsules is also widespread [12].…”
Section: Introductionmentioning
confidence: 99%
“…Wheat flour enhancement using proteinrich materials including cereal and non-cereal sources had been discussed by previous studies to increase its protein content, to improve the essential amino acid balance in the products, add more functional nutritional value of the resultant baked products, and to prevent worldwide protein-energy malnutrition. Consumer acceptability of the new developed products is an important issue of its success (Amir et al, 2013, Ogur, 2014.…”
Section: Introductionmentioning
confidence: 99%